2001
DOI: 10.1007/s004240100025
|View full text |Cite
|
Sign up to set email alerts
|

Indices of iron status in patients treated by chronic haemodialysis

Abstract: Iron deficiency in patients with end stage renal disease (ESRD) treated by haemodialysis (HD) is difficult to diagnose. The reticulocyte hemoglobin content (CHr) and the percentage of hypochromic red cells (%hypo) are sensitive novel assays for the detection of functional iron deficiency in patients treated with erithropoietin (EPO). In our study thirty-nine chronically hemodialyzed patients were evaluated to determine the value of these two parameters in comparison to the conventional biochemical indicators o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
2

Year Published

2004
2004
2005
2005

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 5 publications
0
1
0
2
Order By: Relevance
“…In a different study, CHr was found to have the highest sensitivity and specificity compared with ferritin, transferrin saturation, and MCV for predicting the absence of bone marrow iron stores [21]. The effect of acute or chronic disease on CHr is not completely clear, though CHr has been found useful in evaluating patients with end-stage renal failure [22,23]. There are relatively few conditions that result in reduced CHr.…”
mentioning
confidence: 98%
“…In a different study, CHr was found to have the highest sensitivity and specificity compared with ferritin, transferrin saturation, and MCV for predicting the absence of bone marrow iron stores [21]. The effect of acute or chronic disease on CHr is not completely clear, though CHr has been found useful in evaluating patients with end-stage renal failure [22,23]. There are relatively few conditions that result in reduced CHr.…”
mentioning
confidence: 98%
“…Η ισχυρότερη συσχέτιση ήταν µεταξύ της CHr και του ποσοστού των υπόχρωµων ερυθρών, παρατήρηση που δηµοσιεύτηκε και από τους Zupan και συν. 246 σε 39 αιµοκαθαιρόµενους ασθενείς και από τους Hackeng και συν. 247 σε 61 αιµοκαθαιρόµενους ασθενείς.…”
Section: στηunclassified
“…Σηµαντική συσχέτιση του sTfR µε τη δόση της ερυθροπιητίνης περιγράφηκε από τους Tarng DC και συν., 248 οι οποίοι εκτός από απλή συσχέτιση, εφάρµοσαν πολυπαραγοντική ανάλυση στα δεδοµένα 91 χρόνιων αιµοκαθαιρόµενων ασθενών, καταλήγοντας ότι τα επίπεδα του sTfR µπορούν να προβλεφθούν από τη δόση της ερυθροποιητίνης, το ποσοστό των υπόχρωµων ερυθροκυττάρων και τη φερριτίνη. Σηµαντική συσχέτιση του ποσοστού των υπόχρωµων ερυθροκυττάρων και της CHr µε τη δόση ερυθροποιητίνης περιγράφηκε από τους Zupan και συν., 246 οι οποίοι αποδίδουν υψηλότερη αξία σε αυτούς τους δείκτες συγκριτικά µε τους κλασικούς βιοχηµικούς δείκτες στη διάγνωση της σιδηροπενίας. Οι Hackeng και συν.…”
Section: στηunclassified